Hugo Grotius as apologist for the Christian religion : a study of his work De veritate religionis Christianae, 1640 - Heering, Jan-Paul (Studies in the history of Christian thought, 2003)
This study deals with Hugo Grotius' famous apologetic work De veritate religionis christianae , the Latin version of a Dutch poem which he wrote in 1620 while imprisoned in Loevestein, entitled Bewijs van den waren godsdienst. The first part of this book examines the genesis of the work and the development of the text. The middle sections give an analysis of the motives that led Grotius to write this work and of the sources he most probably used. The final chapters examine the notes that Grotius added to his work in 1640 and the reception of the work in the author's lifetime. The book is illustrated with several historical drawings and prints of Grotius and his time.